Layering engagement: the temporal dynamics of transmedia television - Evans, Elizabeth (University of Nebraska Press, 2015)
The last fifteen years have seen dramatic changes in the UK within both the television industry and televisual storytelling techniques. Rapid technological changes have not only increased the variety of screen devices, they have also changed the boundaries of the industry itself as the internet opened up distribution avenues and alternatives for viewer attention in the form of social media. The traditional pillars of the UK television industry, the major broadcasters and content providers such as the BBC and ITV, have responded to these changes by expanding their focus away from the television set and onto newer, more portable screen devices. This shift has had consequences both for the kinds of narratives emerging from television and the experiences that such narratives craft for their audiences. Increasingly, transmedia storytelling (Jenkins, 2006) techniques are becoming ‘quotidian’ (Grainge and Johnson, 2015), part of television programming’s standard repertoire of narrative techniques. This article examines the relationship between industry strategy and transmedia storytelling techniques. By considering how television studies can look to its own past and re-appropriate foundational models to understand these strategies, this article examines how the changes to television’s narratives exist in a context of both change and continuity.